2020
DOI: 10.1002/ptr.6855
|View full text |Cite
|
Sign up to set email alerts
|

Piperine: A review of its biological effects

Abstract: Medicinal plants have been used for years as a source of food, spices, and, in traditional medicine, as a remedy to numerous diseases. Piper nigrum, belonging to the family Piperaceae is one of the most widely used spices all over the world. It has a distinct sharp flavor attributed to the presence of the phytochemical, piperine. Apart from its use as a spice, P. nigrum is frequently used for medicinal, preservation, and perfumery purposes. Black pepper contains 2–7.4% of piperine, varying in content is associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
106
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 213 publications
(133 citation statements)
references
References 158 publications
2
106
0
Order By: Relevance
“…Alkaloids inhibit dipeptidyl peptidase-4 (DDP-4), for example, bebeerine that degrades gut incretin hormones, including glucagon-like peptide-1 (GLP-1) and gastric inhibitory polypeptide (GIP). A peptide that induces β-cell differentiation stimulates insulin biosynthesis and release, inhibits gastric emptying, directly reducing food intake and prevents glucagon release from the α-cells of the islets of Langerhans [ 20 , 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Alkaloids inhibit dipeptidyl peptidase-4 (DDP-4), for example, bebeerine that degrades gut incretin hormones, including glucagon-like peptide-1 (GLP-1) and gastric inhibitory polypeptide (GIP). A peptide that induces β-cell differentiation stimulates insulin biosynthesis and release, inhibits gastric emptying, directly reducing food intake and prevents glucagon release from the α-cells of the islets of Langerhans [ 20 , 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…5). Piperine is a natural alkaloid in black pepper that possesses important therapeutic properties 96 and has been proposed as a potential inhibitor of SARS-CoV-2 RNAdependent RNA polymerase on the basis of molecular docking simulations. 97 Only two previous studies reported the occurrence of piperine in wastewater 98 or wastewater-impacted surface waters, 99 but neither of them quantied its actual concentration.…”
Section: Nontarget Screening Of Unknown Substances In Wastewatermentioning
confidence: 99%
“…The biological activities of black pepper are attributed to its piperine content, which is the extraction of alkaloid from black pepper. As the major constituent of pepper, piperine exhibited various pharmacological activities, e.g., antifungal (Phuna et al, 2020), antipyretic (Haq et al, 2021), anti-diarrhoeal (Goyal, 2017), analgesic (Chen et al, 2017), and anti-inflammatory activities (Li et al, 2016a;El-Ghazaly et al, 2020). However, the pharmaceutical activities and therapeutic properties of piperine are limited due to its poor water solubility.…”
Section: Introductionmentioning
confidence: 99%